Performance of Depositor Fund: A Lesson from Indonesian Islamic Banking System - Sayakhmad Olimov; Abdul Hamid; Muhammad Arief Mufraini (Faculty of Economic and Business, 2017)
The objective of study is to analyze the performance of Depositor Fund in the operation of Islamic bank as an alternative banking sector in financial market based on the profit and loss mode of financing in the case of Indonesia. The research methodology is quantitative analysis based on the Multiple Regression. In the study secondary data is used and were collected from Annual Report of Islamic Banks. The sample of study is the bank, which is selected from 36 samples of Islamic Commercial Banks relates to non-probability purposive sampling method as a statistical research techniques. The result of study showed that the performance of Depositor Fund in the operation of Islamic banks has negative proficiency and otherwise the Islamic banks have weaknesses capability to improve the high ratio of increasing productivity Depositor Fund based on the financial ratio factors, which are analyzed.DOI: 10.15408/etk.v16i1.4871